A Superhumanization Bias in Whites' Perceptions of Blacks. (April 2015) - Waytz, Adam; Hoffman, Kelly Marie; Trawalter, Sophie
The present research provides the first systematic empirical investigation into superhumanization, the attribution of supernatural, extrasensory, and magical mental and physical qualities to humans. Five studies test and support the hypothesis that White Americans superhumanize Black people relative to White people. Studies 1–2b demonstrate this phenomenon at an implicit level, showing that Whites preferentially associate Blacks versus Whites with superhuman versus human words on an implicit association test and on a categorization task. Studies 3–4 demonstrate this phenomenon at an explicit level, showing that Whites preferentially attribute superhuman capacities to Blacks versus Whites, and Study 4 specifically shows that superhumanization of Blacks predicts denial of pain to Black versus White targets. Together, these studies demonstrate a novel and potentially detrimental process through which Whites perceive Blacks.